The ancient aesthetics of deception the ethics of enchantment from Gorgias to Heliodorus - Grethlein, Jonas 1978- (Cambridge University Press, 2021)
The concept of mimesis has dominated reflection on the nature and role, in Greek literature, of representation. Jonas Grethlein, in his ambitious new book, takes this reflection a step further. He argues that, beyond mimesis, there was an important but unacknowledged strand of reflection focused instead on the nuanced idea of apatē (often translated into English as 'deceit'), oscillating between notions of 'deception' and 'aesthetic illusion'. Many authors from Gorgias and Plato to Philo, Plutarch and Clement of Alexandria used this key concept to entwine aesthetics with ethics. In creatively exploring the various reconfigurations of apatē, and placing these in their socio-historical contexts, the book offers a bold new history of ancient aesthetics. It also explores the present significance of the aesthetics of deception, unlocking the potential of ancient reflection for current debates on the ethical dimension of representation. It will appeal to scholars in classics and literary theory alike
Title from publisher's bibliographic system (viewed on 23 Aug 2021)
Gorgias and the justice of tragic apatē -- The circulation and significance of apatē in the Classical era in the Classical era -- The dramatic entanglement of aesthetic illusion with deceit in Sophocles' Electra -- Immersion and corruption in Plato's Republic -- The void of Hellenistic criticism -- The appeal and challenge of apatē in Imperial criticism: Plutarch's De audiendis poetis -- Lucian and the spell of philosophy -- How to read ekphrasis: Tabula Cebetis -- Christian polemics against idolatry: Clement of Alexandria's Protrepticus -- The aesthetics of deception reconfigured in Heliodorus' Ethiopica -- From deep-fake to psychotherapy: The aesthetics of deception today
Keywords: Greek literature / History and criticism; Aesthetics in literature; Deception in literature; Literatur; Griechisch; Mimesis